A Study of Relation between Force and Acceleration Signals in Airbag Control by Single Pendulum Model - Tran, Trong Dat; Dam, Hoang Phuc; Truong Dang, Viet Thang (Old Journal, 2019)
This paper uses a pendulum collision model to study collision in airbag system design and testing which overcome the disadvantages of the current airbag system testing process. The pendulum model used in this study can change the hardness, mass of the vehicle, collision velocity. In addition, the model can measure acceleration and force during the collision. The paper investigated the dependence of force and acceleration according to factors such as collision mass, collision speed, and equivalent stiffness of the vehicle to evaluate the model. These results can also be used in other studies to determine airbag control algorithm for different vehicles and collision conditions.